A case of successful surgical treatment for peritoneal seeding of hepatocellular carcinoma after radiotherapy and atezolizumab plus bevacizumab combination treatment - Yuri Cho; Bo Hyun Kim; Tae Hyun Kim; Young Hwan Koh; Joong-Won Park (Korean Liver Cancer Association, 2023)
Peritoneal seeding of hepatocellular carcinoma (HCC) is incurable and has poor prognosis. A 68-year-old man underwent surgical resection for a 3.5 cm single nodular HCC at the tip of segment 3 and transarterial chemoembolization for a 1.5 cm-sized recurrent HCC at the tip of segment 6. 3 months later, an increasing 1 cm pelvic nodule on the rectovesical pouch warranted radiotherapy. Although it stabilized, a new 2.7 cm-sized peritoneal nodule in the right upper quadrant (RUQ) omentum appeared 3.5 years after radiotherapy. Hence, omental mass and small bowel mesentery mass excision were performed. 3 years later, recurrent peritoneal metastases in the RUQ omentum and rectovesical pouch progressed. 33 cycles of atezolizumab and bevacizumab treatment elicited stable disease response. Finally, laparoscopic left pelvic peritonectomy was performed without tumor recurrence. Herein, we present a case of HCC with peritoneal seeding that was successfully treated with surgery after radiotherapy and systemic therapy, leading to complete remission.